The Influence of Clean Water Sources on Stunting Incidents - Yuswita, Yuswita; Nuraina, Nuraina; Rahmah, Siti; Liananiar, Liananiar; Raudhati, Sri (Indonesian Journal of Global Health Research, 2024)
Stunting is a significant problem that Indonesia must overcome to produce an excellent cognitive and physical development generation. Stunting is a problem in Bireuen Regency, Indonesia, and must be managed because it has long-term impacts on the future generation. This research is very important to carry out, until now there has been no research on the influence of clean water sources on the incidence of stunting, especially in Bireuen Regency. Research conducted in 137 developing countries shows that clean water sources influence the incidence of stunting. Poor access to clean water the incidence of infectious diseases, so that energy and nutrition for growth and development are diverted by the body's resistance to infectious diseases. The purpose of this research was to find out the effect of clean water source and latrine ownership on stunting occurrence. The study used an analytical, quantitative method with a cross-sectional approach. The research approach to analyze the influence of clean water sources on the incidence of stunting in Pandrah District used quantitative analytical methods with a cross-sectional approach. The sampling technique in this research was a total population of 62 people. Data were analyzed univariately and bivariately, univariate analysis was descriptive while bivariate analysis used the chi-square test to analyze the influence of each independent variable and dependent variable. The research results showed that clean water source had a significant influence on stunting occurrence, with a p-value of 0.002 (which is less than the significance level of 0.05). It could be concluded that clean water source significantly influences stunting occurrence.